How Ecology, Economics, and Ethics Brought Winstanley and Nitobe to Quakerism - Komashin, Stephanie Midori (Quaker studies, 2017)
Gerrard Winstanley, the seventeenth-century English leader of the True Levellers, as they called themselves, a Dissenter group better known as the Diggers, and Inazo Nitobe, co-founder of the nineteenth-century Sapporo Band in Japan and Under-Secretary-General of the League of Nations, were both involved in founding indigenous Christian movements but ultimately joined the Religious Society of Friends. Their views about agricultural ecology, personal financial troubles and ethical commitments led them to Quakerism. Each believed there was no separation of the ethical, spiritual and secular within the experience of nature and ecological cultivation, and shared a commitment to earthcare, sustainable farming, non-violence and ethical living.